The Government’s Prevention Efforts on Violence Against Women Human Rights Perspective - Tanti Kirana Utami (Universitas Kuningan, 2021)
Women are vulnerable to discrimination or violence from other parties. Accordingly, the government needs to make various efforts to protect women's rights and to prevent violence. The study aims to examine the factors and the government's prevention efforts to violence against women. The study employed the normative-juridical method. The study found some factors causing violence against women, such as an individual, partner, socio-cultural, and economic factors. Meanwhile, the governments' efforts cover increasing cooperation with National Commission on Violence against Women and other stakeholders, disseminating various laws and regulations on women's legal protection, advocacy, and women empowerment.